2001
DOI: 10.1002/1529-0131(200109)44:9<2160::aid-art369>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of murine collagen-induced arthritis by ex vivo extracellular superoxide dismutase gene transfer

Abstract: Objective Superoxide dismutase (SOD) is a potent antiinflammatory enzyme that has received growing attention for its therapeutic potential. This study was undertaken to examine the efficacy of extracellular SOD (EC‐SOD) gene therapy in murine collagen‐induced arthritis. Methods Embryonic DBA/1 mouse fibroblasts were infected with a recombinant retrovirus expressing human EC‐SOD. DBA/1 mice that had been treated with type II collagen were administered subcutaneous injections of 2 × 107 EC‐SOD–expressing fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…We found that mitochondrial alterations are significantly reduced in the presence of SOD and NAC, coupled with a reduction in mitochondrial genome mutagenesis, a decrease in oxidative stress levels, and altered mitochondrial membrane potential. Previous studies using mouse models of arthritis showed reduced levels of proinflammatory cytokines after treatment with SOD (43). Furthermore, the finding of increased numbers of blood vessels in SOD-1 Ϫ/Ϫ mice (44) suggests that ROS play a role in regulation of angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…We found that mitochondrial alterations are significantly reduced in the presence of SOD and NAC, coupled with a reduction in mitochondrial genome mutagenesis, a decrease in oxidative stress levels, and altered mitochondrial membrane potential. Previous studies using mouse models of arthritis showed reduced levels of proinflammatory cytokines after treatment with SOD (43). Furthermore, the finding of increased numbers of blood vessels in SOD-1 Ϫ/Ϫ mice (44) suggests that ROS play a role in regulation of angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…-associated oxidative stress by enhancing ecSOD has been applied successfully in various experimental disease models [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (Table I). For example, ecSOD has been shown to restore erectile function in streptozotocin-induced diabetes, 33 protect against vascular dysfunction with aging, 19 blunt ischemia/reperfusion-induced liver injury, 32 reduce systemic vascular resistance and arterial pressure in spontaneously hypertensive rats, 21 improve endothelial dysfunction in hypertension and in heart failure models, 23,35 and ameliorate inflammatory arthritis.…”
Section: Decreasingmentioning
confidence: 99%
“…For example, ecSOD has been shown to restore erectile function in streptozotocin-induced diabetes, 33 protect against vascular dysfunction with aging, 19 blunt ischemia/reperfusion-induced liver injury, 32 reduce systemic vascular resistance and arterial pressure in spontaneously hypertensive rats, 21 improve endothelial dysfunction in hypertension and in heart failure models, 23,35 and ameliorate inflammatory arthritis. 28,29 In most of the aforementioned studies, human ecSOD gene transfer was employed to augment ecSOD activity in animal models. Regarding the behavior and fate of the delivered foreign gene in recipient hosts, most studies showed an increase of ecSOD activity, with a corresponding decrease in levels, after gene transfer (Table I).…”
Section: Ecsod and Experimental Gene Transfermentioning
confidence: 99%
“…83 To affect cytokine, adhesion molecules and MMP gene expression small dsDNA oligonucleotides containing the NF-kB binding site were used to serve as decoys and compete for binding of NF-kB at the transcriptional level. 84,43,45 Therapeutic interventions to ameliorate the formation of free radicals, which mediate part cartilage and bone destruction via oxidative stress, include expression of extracellular superoxide dismutase (EC-SOD) from syngeneic fibroblasts 85 injected s.c. or in combination with catalase from immortalized syngeneic synoviocytes injected i.a. or s.c. 86 To inhibit matrix metalloproteinase (MMP) activity, TIMP-1 was expressed from an adenovirus vector injected i.v.…”
Section: Other Cell Typesmentioning
confidence: 99%